Spectrum of mutations and their phenotypic manifestations in children and adults with long QT syndrome - N. N. Chakova; S. M. Komissarova; E. A. Zasim; T. V. Dolmatovich; E. S. Rebeko; S. S. Niyazova; E. V. Zaklyazminskaya; L. I. Plashchinskaya; M. V. Dudko (Российский кардиологический журнал, 2021)
Aim. To determine the spectrum of mutations in the genes responsible for the long QT syndrome (LQTS) and study their phenotypic manifestations in patients with LQTS in different age groups.Materials and methods. The study included 35 unrelated probands with a clinical diagnosis of LQTS: 23 adults (8 men) and 12 children (9 boys). There were following clinical features: syncope — 54%, positive family history for SCD — 29%, implanted cardioverter defibrillator (ICD) — 46%. All participants underwent 12-lead electrocardiography (ECG), 24-hour Holter monitoring, genealogical analysis, echocardiography and cardiac MRI. The genetic study was performed by nextgeneration sequencing (NGS) using the MiSeq system (Illumina). The quantitative comparison of two unrelated groups was carried out using the nonparametric MannWhitney U-test. The differences were considered significant at p<0,05.Results. In the examined group of 35 probands, 23 genetic variants of pathogenicity class IV and V (hereinafter referred to as) were identified. The molecular genetic variant of the disease was verified in 66% of probands. At the same time, the detection of mutations in the group with early manifestation (children) was significantly higher: 83% (10 out of 12 children) vs 57% in adults (13 out of 23). Rare genetic variants of uncertain significance (VUS, class III pathogenicity) were detected in 4 probands (11%). In the groups of children and adults with LQT1, LQT2 and LQT3, the sex distribution deviated from the 1:1 ratio. Among children, two-thirds were boys, among adults — the same proportion was represented by women. Disease manifestation time, QTc duration and adverse events risk depended on the genetic type of LQTS, intragenic localization of mutations and sex. In children, all 4 missense mutations in the KCNQ1 gene were located in transmembrane domain, and in adults, 4 mutations were in the transmembrane domain and three — in the C-terminal domain of the protein. LQT1 in boys was characterized by early manifestation, while QTc did not exceed 500 ms and there were no adverse outcomes. Two women out of 7 adults with LQT1 with mutations in the transmembrane domain had na ICD (QTc >520 ms). All patients with LQT2 (4 children, 4 adults) had QTc >500 ms. At the same time, 2 children and 3 women had an ICD. LQT3 was diagnosed only in the children subgroup (2 boys, with QTc of 510 ms and QTc of 610 ms); one of them died suddenly despite beta-blocker therapy. Four adult patients, carriers of class III pathogenicity variants, had QTc <500 ms and delayed disease manifestation (after 30 years). Three of them had episodes of clinical death with subsequent resuscitation and implantation of cardioverter defibrillator.Conclusion. The average diagnostic efficiency of mutation identification using NGS in patients with clinically manifest LQTS was 66%. At the same time, mutations were more common in the children’s group. In genotype-positive probands, the risk of adverse outcomes correlated with sex, age and the genetic variant of disease. The greatest number of adverse outcomes was observed in carriers of mutations in both KCNH2 (LQT2) and SCN5A (LQT3) genes. Variants with unknown clinical significance were identified in 4 probands (11%), which potentially allowed to confirm the diagnosis after functional tests.